2017
DOI: 10.1002/2016ja023825
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide trends in the mesosphere and lower thermosphere

Abstract: We investigated trends of carbon dioxide (CO2) in the upper atmosphere, using data from the Atmosphere Chemistry Experiment Fourier Transform Spectrometer and from the Sounding of the Atmosphere using Broadband Emission Radiometry. Recent analyses of these measurements had indicated that CO2 above approximately 90 km appeared to be increasing about twice as fast as it was in the lower atmosphere. Models could not reproduce this differential CO2 trend, calculating instead that the proportional CO2 increase is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 33 publications
6
34
0
1
Order By: Relevance
“…In addition, there is close resemblance between the vertical profile shapes for the SABER data (blue) and WACCM‐sub (red), although the absolute values do not agree. Furthermore, we should also note that the SABER bimonthly relative trend is about 8% per decade around 1 × 10 −4 mb (110 km), which is consistent (within error bars) with those derived in Qian et al (). We would like to stress that the agreement between our results, when accounting for the 60‐day binning, and Qian et al () rules out the deseasonalization as the cause of the discrepancy, as claimed in Qian et al (; (see Appendix ).…”
Section: Trends Analysis Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, there is close resemblance between the vertical profile shapes for the SABER data (blue) and WACCM‐sub (red), although the absolute values do not agree. Furthermore, we should also note that the SABER bimonthly relative trend is about 8% per decade around 1 × 10 −4 mb (110 km), which is consistent (within error bars) with those derived in Qian et al (). We would like to stress that the agreement between our results, when accounting for the 60‐day binning, and Qian et al () rules out the deseasonalization as the cause of the discrepancy, as claimed in Qian et al (; (see Appendix ).…”
Section: Trends Analysis Resultssupporting
confidence: 91%
“…The SABER instrument description and characteristics, including satellite orbit and the viewing direction, are originally described in Russell et al (), and also briefly reviewed in works already mentioned (e.g., Qian et al, ; Rezac, Kutepov, et al, ; Yue et al, ). The SABER CO 2 VMR data are post‐operationally retrieved simultaneously with temperatures, however, only for daytime conditions (solar zenith angle <80°) as detailed in Rezac, Kutepov, et al ().…”
Section: Sd‐waccm and Saber Datamentioning
confidence: 99%
“…Recent results from SABER (Sounding of the Atmosphere using Broadband Emission Radiometry) observations showed that the CO 2 vmr trend is ~5%/decade up to ~80 km and ~12% at ~110 km in the latitude range of ±54° during 2002–2014 (Yue et al, ). However Qian et al () found the CO 2 trends of ~5.5%/decade above ~90 km, which are consistent with that of lower atmosphere using the corrected SABER observations for 2002–2016.…”
Section: Introductionmentioning
confidence: 53%
“…The CO 2 is well mixed in troposphere (~0–15 km) and stratosphere, and the eddy diffusion leads to its constant vmr even up to ~80–90 km. The CO 2 vmr decreases exponentially above this height due to photolysis (CO 2 + hν → CO + O( 1 D) at λ ~ 120–210 nm) and increasing molecular diffusion (e.g., Garcia et al, ; Qian et al, ; Rezac et al, ; Yue et al, ). Recent results from SABER (Sounding of the Atmosphere using Broadband Emission Radiometry) observations showed that the CO 2 vmr trend is ~5%/decade up to ~80 km and ~12% at ~110 km in the latitude range of ±54° during 2002–2014 (Yue et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Trends in the temperature are being reported using the long-term measurements from network of radiosondes (Philipona et al, 2018, and references therein), Rayleigh lidars (Kishore et al, 2014), and satellite observations (Akhil Raj et al, 2018;Huang et al, 2014;Randel et al, 2017, and references therein). Few modeling studies are also made to understand the mechanisms behind the observed changes (Fomichev et al, 2007;Garcia et al, 2007;Lübken et al, 2013;Qian et al, 2017Qian et al, , 2019. From these studies, significant decreasing trend in the zonal wind in the middle mesosphere and no significant trend in the upper mesosphere using network of MF/Meteor radars in the equatorial latitudes is observed.…”
Section: Introductionmentioning
confidence: 99%